Russia,1828
includes letters from: Richard Knill, St Petersburg - book of Isaiah in Persian by Mr Glen (Scottish missionary); provision for missionaries' widows and orphans; special contributions for work in other mission fields William Swan, Selenginsk - New Testament in Mongolian received, suggests some sent to India (for Tibet); success or lack of it Robert Yuille, Selenginsk - 2 missionaries needed at each station (in Siberia), one to teach and one to visit, if only a single station with 2 missionaries can be sustained it should be at the Ona; time has come for a printer to be sent; future of Selenginsk work; daily services; callers from another tribe; borrowed lamas' book to copy Edward Stallybrass, Selenginsk - future policy, must be willing to move on from original base despite expense; joint letter from Robert Yuille, William Swan and Edward Stallybrass, Selenginsk - decision to separate, William Swan going to house on the Ona, Edward Stallybrass to Khodon; request new staff for Selenginsk; translation revision; removal to Khodon; family prayers with Buryats; house burnt down (postscript by Richard Knill, St Petersburg to Royston and Stepney churches in England to replace the house John Paterson, Edinburgh - Cornelius Rahmn's offer to return to Selenginsk